Multiobjective design of automobile composite applications based on feasibility robustness - Carlos Conceição António (2015)
In the proposed multi-objective optimization approach the weight and the determinant of the variance-covariance matrix of the response of composite structures used in automobile applications are considered as performance and robustness functions, respectively. The Pareto front is built using a modified version of previously proposed hierarchical genetic algorithm with co-evolution of populations here denoted by MOGA-2D.